Reframing Biology Learning through Project-Based Learning: Evidence from the Digestive System - Sembiring, Al Khudri; Dinata, Marta; Novi Ariska, Raja; Dongoran, Jhonas (Biosfer: Jurnal Tadris Biologi, 2026)
This study aimed to investigate the effect of Project-Based Learning on eleventh grade students’ higher-order cognitive learning outcomes and learning activities in biology. A quasi-experimental design with a pretest-posttest control group was employed involving 66 students from SMA Negeri 1 Teluk Kuantan, Indonesia. The participants were divided into an experimental group receiving Project-Based Learning and a control group receiving conventional instruction. Data were collected using a cognitive achievement test based on the revised Bloom taxonomy at the levels of analyzing, evaluating, and creating, as well as structured observation sheets to assess students’ learning activities. The data were analyzed using descriptive statistics, independent-samples t-tests, and normalized gain analysis. The results revealed that the experimental group achieved a higher mean posttest score (82.62) than the control group (73.13), with a statistically significant difference (p < .05). The experimental group also demonstrated a higher normalized gain score (0.65) compared with the control group (0.47). Furthermore, students’ learning activities in the experimental class increased consistently across the intervention, rising from 78.79% to 87.88%. These findings indicate that Project-Based Learning effectively promotes higher order thinking and active engagement in biology learning. The study contributes to the literature by integrating cognitive outcomes and observable learning activities within a single analytical framework, offering practical implications for the implementation of student-centered instruction in secondary biology education.  Mereposisi Pembelajaran Biologi melalui Project-Based Learning: Bukti pada Materi Sistem Pencernaan Manusia ABSTRAK: Penelitian ini bertujuan untuk menganalisis pengaruh Project-Based Learning terhadap hasil belajar kognitif tingkat tinggi dan aktivitas belajar peserta didik kelas XI pada mata pelajaran biologi. Penelitian ini menggunakan desain kuasi eksperimen dengan pola pretest-posttest control group yang melibatkan 66 peserta didik dari SMA Negeri 1 Teluk Kuantan, Indonesia. Partisipan dibagi ke dalam kelompok eksperimen yang memperoleh pembelajaran berbasis proyek dan kelompok kontrol yang mengikuti pembelajaran konvensional. Data dikumpulkan menggunakan tes hasil belajar kognitif yang disusun berdasarkan taksonomi Bloom revisi pada level menganalisis, mengevaluasi, dan mencipta, serta lembar observasi terstruktur untuk mengukur aktivitas belajar peserta didik. Data dianalisis menggunakan statistik deskriptif, uji independent samples t test, dan analisis normalized gain. Hasil penelitian menunjukkan bahwa kelompok eksperimen memperoleh rerata nilai posttest yang lebih tinggi (82,62) dibandingkan kelompok kontrol (73,13), dengan perbedaan yang signifikan (p < 0,05). Kelompok eksperimen juga menunjukkan nilai normalized gain yang lebih tinggi (0,65) dibandingkan kelompok kontrol (0,47). Selain itu, aktivitas belajar peserta didik pada kelas eksperimen mengalami peningkatan yang konsisten selama intervensi, dari 78,79% menjadi 87,88%. Temuan ini menunjukkan bahwa Project-Based Learning efektif dalam meningkatkan kemampuan berpikir tingkat tinggi dan keterlibatan aktif peserta didik dalam pembelajaran biologi. Penelitian ini berkontribusi pada pengembangan kajian pendidikan biologi dengan mengintegrasikan hasil belajar kognitif dan aktivitas belajar dalam satu kerangka analisis, serta memberikan implikasi praktis bagi penerapan pembelajaran yang berpusat pada peserta didik di pendidikan menengah